2013
DOI: 10.4236/eng.2013.512117
|View full text |Cite
|
Sign up to set email alerts
|

Macro Rain Water Harvesting Network to Estimate Annual Runoff at Koysinjaq (Koya) District, Kurdistan Region of Iraq

Abstract: Macro rainwater harvesting techniques (Macro RWH) are getting more popular to overcome the problem of water scarcity in arid and semi-arid areas. Iraq is experiencing serious water shortage problem now despite of the presence of Tigris and Euphrates Rivers. RWH can help to overcome this problem. In this research, RWH was applied in Koya City in its districts, North West Iraq. Twenty-two basins were identified as the catchment area for the application of RWH technique. Watershed modeling system (WMS), based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…(Challenge 1):For environmentalists working in such anthropogenic ally modified systems (e.g., agricultural landscapes, urban areas or forest production) challenges stand up in (i) the determination of human influence on service-providing units and related ecosystem services and (ii) considering the impact of landscapes nearby land units that provide ecosystem services. Urban preparation that considers the fixing of green infrastructure in towns such as road trees and gardens may benefit biodiversity and many ecosystem services (e.g.,air filtration, water regulation, and noise decrease [45,46]. Ecologists can directly donate to ecosystem service studies and help policy decisions, not only by estimating human impact, but also by suggesting anthropogenic interventions to benefit ecosystem services and service-providing units.…”
Section: Challenges A) Understanding Anthropogenic Ally Modified Systemsmentioning
confidence: 99%
“…(Challenge 1):For environmentalists working in such anthropogenic ally modified systems (e.g., agricultural landscapes, urban areas or forest production) challenges stand up in (i) the determination of human influence on service-providing units and related ecosystem services and (ii) considering the impact of landscapes nearby land units that provide ecosystem services. Urban preparation that considers the fixing of green infrastructure in towns such as road trees and gardens may benefit biodiversity and many ecosystem services (e.g.,air filtration, water regulation, and noise decrease [45,46]. Ecologists can directly donate to ecosystem service studies and help policy decisions, not only by estimating human impact, but also by suggesting anthropogenic interventions to benefit ecosystem services and service-providing units.…”
Section: Challenges A) Understanding Anthropogenic Ally Modified Systemsmentioning
confidence: 99%
“…The rainwater harvesting has the ability to ensure availability of water for the region [30] as well. The effective management of RWH becomes more interesting phase of water resource management strategies in most countries that are suffering from the problem of water scarcity [31].…”
Section: Validity Of Rain Water Harvestingmentioning
confidence: 99%
“…Zakaria et al [31] identified twenty two basins around Koya, Erbil Governorateat north east of Iraq, as the catchment area for the application of RWH technique in order to evaluate the total runoff from whole Koya area that may be harvested instead of being lost to the near area. Two consecutive adjustments for the curve number were considered.…”
Section: Application Of Rwh In Iraqmentioning
confidence: 99%
See 1 more Smart Citation
“…Along with multispectral data, GIS tools enhanced this study by mapping soil properties. GIS manipulated the soil properties as attributes and helped visualize the study site's soil classification [33][34][35][36]. The current study's main objectives are: 1) To examine the potential of geoinformatics techniques to depict, map, and assess the iron-rich soils in the study region using the Landsat -7 ETM+ image, 2) To process the ETM+ image and retrieve band details and other spectral indices for soil analysis, 3) To generate a statistical regression model between the spectral indices retrieved from satellite image and soil lab data and test the predicted models' significance.…”
Section: Introductionmentioning
confidence: 99%